The Incidence of Shoulder Injury among Collegiate Overhead Athletes - Kevin Laudner; Rob Sipes (University of Kansas Libraries, 2009)
Shoulder injury in overhead athletes, who perform repetitive overhead motions, has been well documented; however, there is a paucity of data regarding the incidence of specific shoulder injuries in these individuals. Data were collected from the preseason medical examinations and medical records maintained throughout the collegiate careers of 371 overhead athletes. Shoulder injuries were documented in 30% of the athletes during their athletic careers. Subacromial impingement syndrome and rotator cuff (RTC) tendonitis were the most common shoulder injuries for each individual sport and accounted for 27% and 24% of the total shoulder injuries respectively. These injuries had a significantly higher incidence rate (p = .001) than any other injury among the athletes. Significant incidence rates were found for baseball players diagnosed with subacromial impingement (p = .001), softball players diagnosed with subacromial impingement and RTC tendonitis (p = .001), swimmers diagnosed with subacromial impingement, RTC tendonitis, and biceps tendonitis (p = .001), and tennis players diagnosed with subacromial impingement and RTC tendonitis (p = .001). No significant incidence rates were found for the number of injured athletes per sport (p = .42) or for the total number of injuries per sport (p = .11). Rotator cuff tendonitis and subacromial impingement syndrome were the most common shoulder injuries reported for each of the five sports.